Exchange options under clustered jumps dynamics - Yong, Ma, author; Pan, Dongtao, author; Wang, Tianyang, author; Quantitative Finance, publisher (Colorado State University. Libraries, 2019)
Exchange options are one of the most popular exotic options, and have important implications for many common financial arrangements and for implied beta as a measure of systematic risk. In this study, we extend the existing literature on exchange options to allow for clustered jump contagion dynamics in each single asset, as well as across assets, using the Hawkes jump-diffusion model. We derive the analytical pricing formulae, the Greeks, and the optimal hedging strategy via Fourier transforms. Using an illustrative numerical analysis, we present the relationship between the exchange option price and clustered jump intensities and jump sizes in the underlying assets. We discuss the managerial insights on financial arrangements with exchange option characteristics. Furthermore, we discuss the implications of incorporating clustered jumps into the estimation of implied beta with exchange options, in which the applications can be insightful and useful in finance practice.
Published as: Quantitative Finance, January 2020, https://doi.org/10.1080/14697688.2019.1704045.
Keywords: exchange option; Hawkes jump-diffusion process; optimal hedging; implied beta; Greeks